Factors affecting 2014 Farm Bill commodity program enrollment factors for Kansas farmers - Wilson, Candice (Kansas State University, 2017)
BACKGROUND AND PURPOSE: The 2014 Farm Bill required Kansas producers to make a series of enrollment decisions that were both complicated and based on incomplete information. With this bill, producers were required to complete a one-time enrollment in one of three programs (ARC-CO, PLC, or ARC-IC) to serve as a safety net for poor crop prices and/or yields over the five-year life of the legislation. Analyzing the effects of incomplete information on producers’ decisions provides an opportunity to identify challenges associated with program selection under the 2014 Farm Bill and suggest changes for future farm support legislation. METHODS: Kansas county-level enrollment data obtained from USDA-FSA are used to model aggregate producer sign-up decisions as a function of estimated 2014 payments, county-level yield variability, prior program enrollment, and extension programming efforts at the county and state level. This OLS model is subsequently replicated using individual producer data from surveys conducted during fifteen extension meetings held across Kansas. The model based on individual data is a regression of stated preferences for the three programs as a function of farm size, farmer demographics, risk preferences, and knowledge of the legislation. RESULTS: Comparisons of model results from the aggregated enrollment data and the individual survey data offer insights into the factors affecting producer decisions. Specifically, aggregate enrollment decisions are difficult to explain given many unobservable enrollment considerations at a county level. However, when the regression is repeated using individual data, other factors affect the enrollment decision such as the number of years a producer has been farming, the size of the farm, their membership in commodity associations, and their risk preferences. CONCLUSIONS: The 2014 Farm Bill required producers to select participation in a single support program for the five-year life of the legislation. This decision had to be made without knowing exactly how crop prices and yields would behave in the future. It is important to understand how producers made their decisions based on incomplete information to inform future legislative efforts for an effective farm safety net. This research expands that understanding by analyzing both aggregate and individual data to determine the factors that influence program choice.
Keywords: Agriculture Economics; Public Policy